Key determinants and trends of development of youth entrepreneurship - Khussainova, Zh.S.; Bektleyeva, D.Ye.; Zhartay, Zh.M. (BUKETOV BUSINESS REVIEW, 2018)
Abstract. In article are investigated key determinants and trends of development of youth business, analytical data on development of business activity among youth are provided. Results of such indicators as the index of early enterprise activity in Kazakhstan in a section of age groups, the index of business activity in Kazakhstan, levels of origin of youth business, distribution of early business activity by sectors of economy are given. Authors recognize that development of business initiatives of youth is that vanguard which is capable to bring domestic national economy to new boundaries. Support of youth business which is necessary for effective realization of social modernization of Kazakhstan becomes the major task. Youth business in today’s Kazakhstan, though experiences considerable difficulties, - already come true fact. In article are reflected modern trends of youth business in Kazakhstan. The general analysis of operating conditions of the Kazakhstan business has shown that development of youth business faces a number of the serious problems containing growth of business activity among youth. At the same time, the main measures of elimination of the existing problems reveal. In article are offered mechanisms of regulation and stimulation of business activity of youth.